The Influence Of Leadership Style And Work Stress On Employee Turnover At PT Cahaya Putra Persada - Amelia Amelia; Asep Jamaludin; Nandang Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study aims to analyze the effect of leadership style and work stress on employee turnover at PT Cahaya Putra Persada. The variables studied were leadership style and work stress in relation to employee turnover. The research method used is a quantitative method. The data used is data collected directly through the distribution of questionnaires to employees of PT Cahaya Putra Persada. The number of samples in this study were 63 employees. Data analysis techniques used include t test, F test, and coefficient of determination test using SPSS 24 software. The results of this study indicate that leadership style (X) has no significant effect on employee turnover. Work stress (X2) has a significant effect on employee turnover. Thus, the results of this study indicate that the factor that has a very significant influence is work stress, which plays a role in the frequent employee turnover at PT Cahaya Putra Persada.